What does safety in mental healthcare transitions mean for service users and other stakeholder groups: An open‐ended questionnaire study. (20th January 2021) - Tyler, Natasha; Wright, Nicola; Panagioti, Maria; Grundy, Andrew; Waring, Justin
Abstract: Background: Historically, safety mental health research has tended to focus on risks of homicide, suicide and deaths. Although wider safety issues are now recognized in regards to mental health services, the safety of mental health transitions, a key research and policy priority according to World Health Organisation, has not been explored. Objective: The purpose of this study was to investigate perceptions of safety in mental health transitions (hospital to community) amongst five stakeholder groups. Design and setting: An online, international cross‐sectional, open‐ended questionnaire. Participants: There were five stakeholder participant groups: service users; families/carers; mental health‐care professionals; researchers; and end users of research. Results: Ninety‐three participants from 12 different countries responded. Three overarching themes emerged: 'individual/clinical', 'systems/services' and 'human, behavioural and social' elements of safe mental health transitions. Whilst there was a great focus on clinical elements from researchers and healthcare professionals, service users and carers considered safety in terms of human, behavioural and social elements of transitional safety (ie loneliness, emotional readiness for discharge) and systems/services (ie inter‐professional communication). Discussion: Safety in mental health‐care transitions is perceived differently by service users and families compared to healthcare professionals and researchers. Traditional safety indicators for care transitions such as suicide, self‐harm and risk of adverse drug events are raised as important. However, service users and families in particular have a much wider perception of transitions safety. Conclusion: Future quality and safety research and policy should consider including a service user voice and consider integration of psychosocial elements in discharge interventions.